Factors Controlling Stable Hydrogen,Oxygen,and Carbon Isotope Ratios in Regional Shallow Groundwater of Guangzhou City,China - ZENG Hui; ZHUO Quanlong; ZHANG Mingzhu; PANG Yuan; LIANG Zuobing (Renmin Zhujiang)
To investigate the distribution characteristics and controlling factors of stable hydrogen,oxygen,and carbon isotopes in shallow groundwater in Guangzhou,18 shallow groundwater monitoring wells in Guangzhou were selected.This study analyzed the component characteristics of stable hydrogen and oxygen isotopes in surface water and groundwater,stable isotopes of dissolved inorganic carbon in groundwater,and ammonium nitrogen isotope in groundwater in Guangzhou City and investigated the influencing factors of groundwater hydrological characteristics and the evolution of dissolved inorganic carbon.The results show that atmospheric precipitation is an important source of shallow groundwater recharge,and there is a close hydraulic connection between groundwater and surface water in Conghua District,northern Guangzhou,where precipitation directly recharges groundwater and is less affected by evaporation;near the southern coastal area of Guangzhou,groundwater may be affected by seawater intrusion.The deuterium excess parameter (d-excess) values in groundwater in Conghua District are significantly influenced by the control of groundwater retention time,and the significantly low d-excess values in the southern coastal area of Guangzhou may be influenced by the seawater intrusion.The evolution of DIC in shallow groundwater is significantly influenced by anthropogenic factors,and the value of δ13CDIC in the water body is higher.In contrast,high-ammonium groundwater mainly comes from the degradation of natural organic matter,and the high concentration of NH+4 is the main reason for the abnormally high δ13CDIC value in groundwater.